Illfection of Vowral Languange Vocational Sikka Krowe in the Use of Pronomina - Maria Ermilinda Dua Lering (Unipdu Jombang, 2021)
The Sikka dialect of Krowe is one of the six languages in Sikka Regency that is unique. The uniqueness of the Krowe dialect is that verbs can reflect. Issues discussed are the change in verbs in the Sikka dialect of Krowe in the use of a single pronoun, the change in verbs in Sikka in the Krowe dialect in the use of plural pronouns and the meaning that arises from these changes. This study aims to determine changes in verbs in the Sikka dialect of Krowe in the use of singular and plural pronouns and changes in meaning as a result of these changes. The approach used is a qualitative approach with descriptive methods. Based on the results of data analysis in the form of words spoken or written by informants, it was found that there was a change in verb when used by a single person pronoun when used a plural persona pronoun, the change was incomplete, it was also found that there was a change in meaning as a result of the change